MODEL BEBAS DAN MEDIA WORDWALL DALAM MENINGKATKAN KETERAMPILAN MENYIMAK, BERPIKIR KRITIS, DAN KOLABORASI MURID SDN SEPAKAT BERSAMA - Herawati, Fitri; Dwitalia Sari, Dessy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low levels of listening, critical thinking, and collaboration skills, as well as the poor learning outcomes, observed among third-grade students at SDN Sepakat Bersama. These issues stemmed from a one-way instructional process and a lack of student engagement, which resulted in limited active participation, insufficient use of technology as an instructional medium, and a lack of student interest and motivation. The study aimed to describe teacher activities and analyze student activities, listening skills, critical thinking, collaboration, and learning outcomes through the implementation of the BEBAS model and Wordwall media. This research employed a Classroom Action Research (CAR) design with a qualitative approach, conducted over two cycles comprising four meetings. The subjects were 16 students during the even semester of the 2025/2026 academic year. Data were collected through interviews, observations, and written tests. The results showed that teacher activity improved from a score of 18 to 24, reaching the